Factors influencing entrepreneurial intention of university students in Yemen: The mediating role of entrepreneurial self-efficacy - Al-Qadasi, Nabil; Zhang, Gongyi; Al-Awlaqi, Mohammed Ali; Alshebami, Ali Saleh; Aamer, Ammar (Frontiers in Psychology, 2023)
The current study investigates the relationships between certain personality traits and environmental and situational factors with the intention to start a new business. Data were collected through a survey responded to by 487 final-year university students from two universities (public and private) in Yemen. The study’s hypotheses were tested using Structural Equation Modeling (SEM). The study revealed that personality traits of the need for achievement and locus of control have a positive relationship with entrepreneurial self-efficacy and entrepreneurial intention. Also, instrumental readiness has a positive relationship with entrepreneurial self-efficacy but not with entrepreneurial intention. Further, situational factors show a positive association with entrepreneurial intention but not with entrepreneurial self-efficacy. Additionally, the relationship between entrepreneurial self-efficacy and entrepreneurial intention was positive. Furthermore, the findings of the study revealed that entrepreneurial self-efficacy mediates the relationship between the need for achievement, locus of control, instrumental readiness, and entrepreneurial intention. However, entrepreneurial self-efficacy did not mediate the relationship between situational factors and entrepreneurial intention. The study provided a slew of recommendations to policymakers and various stakeholders.